De la reliquia al souvenir - García Escalona, Emilia (Revista de Filología Románica, 2006)
The travelling experience through souvenirs, which can become relics, and their variety in a global consumers’society, is the topic of this article. The meaning of the souvenir, its symbols, and its selling points. The mixture of high and low culture in what the cities offer to the tourist, and the image of the cities in its souvenirs.